2013
DOI: 10.1108/itp-09-2012-0098
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic influences on health information searching in the USA: the case of diabetes

Abstract: 2014),"Why do people stick to Facebook web site? A value theorybased view", Information Technology & People, Vol. 27 Iss 1 pp. 21-37 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Passive information-seeking activities involve reading the newspaper and watching television, whereas active information seeking involves mainly using the internet as a source of health information [ 17 , 18 ]. Morgan and Trauth [ 20 ] used the Integrated Model of E-Health Use developed by Dutta-Bergman [ 21 ] to investigate eHealth information–seeking behavior among persons with diabetes in Greece. The authors [ 20 ] found that people with diabetes exhibited different health information–searching behavior because of the intrinsic motivation resulting from access to health care providers or resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive information-seeking activities involve reading the newspaper and watching television, whereas active information seeking involves mainly using the internet as a source of health information [ 17 , 18 ]. Morgan and Trauth [ 20 ] used the Integrated Model of E-Health Use developed by Dutta-Bergman [ 21 ] to investigate eHealth information–seeking behavior among persons with diabetes in Greece. The authors [ 20 ] found that people with diabetes exhibited different health information–searching behavior because of the intrinsic motivation resulting from access to health care providers or resources.…”
Section: Introductionmentioning
confidence: 99%
“…Morgan and Trauth [ 20 ] used the Integrated Model of E-Health Use developed by Dutta-Bergman [ 21 ] to investigate eHealth information–seeking behavior among persons with diabetes in Greece. The authors [ 20 ] found that people with diabetes exhibited different health information–searching behavior because of the intrinsic motivation resulting from access to health care providers or resources.…”
Section: Introductionmentioning
confidence: 99%
“…They act as answerers, scholars and experts in the social Q&A community (Kim and Oh, 2009; Jeng et al , 2017; Neshati et al , 2017). On the other hand, users are regarded as information consumers (Shao, 2009; Janeice Morgan and Trauth, 2013; Liu et al , 2019) or information seekers (Shah et al , 2014; Liu and Jansen, 2017), who search for answers, knowledge and discussion content. According to users' posting behaviors, previous studies have classified users into active users and lurkers in the online community (Marett and Joshi, 2009; Yang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For diseases such as cancer, in earlier days a death sentence for many has spawned an entire network of communications and information [3][4][5]. The same goes for diabetes [6] and for heart disease [7]. As a consequence, medical information, may be getting increasingly dense over time as medicine advances and the literature and alternative options become overwhelming, for example the "BELONG" community of cancer patients [8].…”
Section: Introductionmentioning
confidence: 99%